Effect of cataract extraction and posterior chamber lens implantation on outflow facility and its response to pilocarpine in Korean subjects. Issue 9 (1st September 2000) - Kee, Changwon; Moon, Seong-Heon
Abstract : AIM: To investigate the effect of the lens on outflow facility in Korean patients with cataracts. METHODS: Intraocular pressure was measured by Goldmann applanation tonometry in 42 patients with cataracts and outflow facility was determined by tonography preoperatively, before and after instillation of pilocarpine. All patients received clear corneal phacoemulsification and silicone foldable intraocular lens implantation within the capsular bag by one surgeon. Two months after surgery, slit lamp examination and gonioscopy were performed and intraocular pressure and outflow facility were again determined. Statistical analysis was carried out using the Student's paired t test. RESULTS: There were no anterior chamber reactions and no visible trabecular meshwork damage 2 months after surgery. Intraocular pressure 2 months after lens extraction decreased by a mean of 2.4 (SE 0.4) mm Hg (p<0.001) compared with the preoperative value; postoperative outflow facility with and without pilocarpine increased by 0.080 (0.019) μl/min/mm Hg (p<0.001) and 0.045 (0.014) μl/min/mm Hg (p<0.001), respectively, at 2 months compared with preoperative values. The facility response to pilocarpine after lens extraction, relative to the baseline value and preoperative response, increased by 10.7 (7.1)% which was not statistically significant (p>0.1). CONCLUSION: Lens extraction causes a reduction in intraocular pressure and an increase in outflow facility in Korean subjects. Pilocarpine causes an increase in outflow facility which persists after cataract extraction and posterior chamber lens implantation.